Application of Modeling Approaches to Explore Vaccine Adjuvant Mode-of-Action - Buckley, Paul R.; Alden, Kieran; Coccia, Margherita; Chalon, Aurélie; Collignon, Catherine; Temmerman, Stéphane T.; Didierlaurent, Arnaud M.; van der Most, Robbert; Timmis, Jon; Andersen, Claus A.; Coles, Mark C. (Frontiers in Immunology, 2019)
Novel adjuvant technologies have a key role in the development of next-generation vaccines, due to their capacity to modulate the duration, strength and quality of the immune response. The AS01 adjuvant is used in the malaria vaccine RTS,S/AS01 and in the licensed herpes-zoster vaccine (Shingrix) where the vaccine has proven its ability to generate protective responses with both robust humoral and T-cell responses. For many years, animal models have provided insights into adjuvant mode-of-action (MoA), generally through investigating individual genes or proteins. Furthermore, modelling and simulation techniques can be utilised to integrate a variety of different data types; ranging from serum biomarkers to large scale ‘omics’ datasets. In this perspective we present a framework to create a holistic integration of pre-clinical datasets and immunological literature in order to develop an evidence-based hypothesis of AS01 adjuvant MoA, creating a unified view of multiple experiments. Furthermore, we highlight how holistic systems-knowledge can serve as a basis for the construction of models and simulations supporting exploration of key questions surrounding adjuvant MoA. Using the Systems-Biology-Graphical-Notation, a tool for graphical representation of biological processes, we have captured high-level cellular behaviours and interactions, and cytokine dynamics during the early immune response, which are substantiated by a series of diagrams detailing cellular dynamics. Through explicitly describing AS01 MoA we have built a consensus of understanding across multiple experiments, and so we present a framework to integrate modelling approaches into exploring adjuvant MoA, in order to guide experimental design, interpret results and inform rational design of vaccines.